Separate aspects nullity of testament - Крат, В. І. (Theory and practice of jurisprudence, 2016)
Problem setting – Nullity is the enough widespread phenomenon in a civil law. The analysis nullity determines a requirement in finding out nullity of testament. Recent research and publications analysis – To the analysis ineffectiveness of testament, in particular, such researchers applied as Bondarev N. I., Maltsman T.B., Eydinova E. B. Paper objective – In notarial practice there was ambiguous attitude toward interpretation of positions of article 1247 the Civil code of Ukraine in the context of that embraces by a soba «time drafting of testament» and whether absence of drafting time influences in a testament on his reality. Position according to that time drafting of testament must include a hour and minute was formed in judicial practice, and unpointing of them results in violation of requirements in relation to the form of testament. Paper main body – The article is sanctified to the separate aspects nullity of testament. Nullity of testament through the prism time drafting of testament is analyzed in the article. Conclusions of the research – Drawn conclusion, that «time drafting of testament»: must contain a date (day, month, year), hour, minute of his drafting; does not belong to the manner and matter of testament; on the essence is the essential 2 element of testament. Absence in the testament of pointing on a hour and minute of his drafting must not have investigation of his nullity.